2009
DOI: 10.1007/s10661-009-1010-x
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater depth and elevation interpolation by kriging methods in Mohr Basin of Fars province in Iran

Abstract: Prediction of groundwater depth and elevation is important in quantitative water management especially in arid areas. There are several basins in southwest of Iran, in Zagross Mountain, in which the water wells are distributed along a narrow elliptic ring band around the region. To find the most applicable interpolation method, both of the groundwater depth and elevation are predicted by different kriging methods. It is found that the groundwater elevation and depth can be predicted by different methods. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 32 publications
0
26
0
2
Order By: Relevance
“…Spatial interpolation of the water table depth from the original ground surface at monthly scale averaging over the 2 years (2014 and 2015) was done over a year using the ordinary kriging option in the Spatial Analyst Tool of ArcGIS. This method was selected because ordinary kriging showed the most acceptable results in groundwater depth interpolation (Nikroo, Kompani‐Zare, Sepaskhah, & Shamsi, ). The interpolation was done for the part of the watershed where groundwater level data was collected, excluding the upper part of the watershed.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial interpolation of the water table depth from the original ground surface at monthly scale averaging over the 2 years (2014 and 2015) was done over a year using the ordinary kriging option in the Spatial Analyst Tool of ArcGIS. This method was selected because ordinary kriging showed the most acceptable results in groundwater depth interpolation (Nikroo, Kompani‐Zare, Sepaskhah, & Shamsi, ). The interpolation was done for the part of the watershed where groundwater level data was collected, excluding the upper part of the watershed.…”
Section: Methodsmentioning
confidence: 99%
“…Ahmadi and Sedghamiz (2008) used OK to evaluate the spatial and temporal variations of groundwater level and found that groundwater level variations have strong spatial and temporal structure. Nikroo et al (2010) conducted OK analysis on water table elevation of non-uniformly spaced observation wells in Iran and found a relatively strong spatial relationship between the water table elevations of the wells. Dash et al (2010) used kriging for optimizing data collection and utility in a regional groundwater investigation and showed that OK is a useful tool to elucidate those areas lacking enough data for developing a water table management network.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a spherical semivariogram resulted in the lowest mean error, average standard error, and root mean square error when compared to pentaspherical and exponential semivariograms. We followed the procedures outlined in [84,85] for semivariogram selection. One kriged map was created for each year.…”
Section: The Neural Network Approach and Input Datamentioning
confidence: 99%